Antioxidant Properties of Lemuni Leaves (Vitex trifolia var. purpurea) in Different Concentrations of Ethanol-Water Solvent Extraction - Wei Wen Goh; Sharmin Sultana; Azrina Azlan (Talenta Publisher, 2024)
Vitex trifolia var. purpurea leaves (Lemuni leaves) is considered as a traditional medicine due to their antioxidant property. The antioxidant properties of Lemuni leaves depends on the concentration of ethanol-water solvent. Therefore, this current study intended to identify the antioxidant activity of Lemuni leaves (Vitex trifolia var. purpurea) in different concentrations of ethanol-water solvent extraction. Four ethanol-water concentrations were prepared (water extract (0% ethanol), 25% ethanol extract, 50% ethanol extract, and 75% ethanol extract). The antioxidant properties of Lemuni leaves were evaluated by Folin-Ciocalteu assay, aluminium chloride calorimetric method while 2,2’-diphenyl-1-picrylhydrazyl (DPPH) assay and 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay were used to measure the antioxidant activities of the extracts. The experimental results showed that 75% ethanol extract had the highest (p<0.05) total phenolic content (94.69 ± 4.75mg GAE/g DW) and total flavonoid content (30.76 ± 2.85mg QE/g DW) significantly. The 75% ethanol extract also had the significantly lowest (p<0.05) IC50 value for DPPH (3.56 ± 0.11 mg/mL) and ABTS (2.01 ± 0.05 mg/mL) assays. Strong correlations were discovered between the total flavonoid content, total phenolic content with antioxidant properties of Lemuni leaves at different ethanol-water ratio by DPPH (r= -0.816; r= -0.824) and ABTS assays (r= -0.929; r= -0.920).The significantly elevated antioxidant properties of the 75% ethanol extract suggest promising applications in health supplements, pharmaceuticals, skincare products, biomedical research, and commercial ventures.